A fundamental study of improving ductility of reinforced high-strength concrete (HSC) members - Omar, Wahid (Universiti Teknologi Malaysia, 2006)
In recent years, the use of high strength concrete (HSC) has become increasingly popular in the construction of buildings and infra-structures. The utilization of HSC has been spurred on by the superior mechanical properties of the material and its cost-effectiveness. However, HSC tends to be more brittle or less tough than normal strength concrete. Therefore, external confinements are used to overcome and enhance the concrete characteristics. This study investigates the effectiveness of using steel straps in increasing the strength and ductility of HSC. Its also investigate the effects of using steel straps with different ultimate tensile strength and placed with different spacings. All the cylinders were tested under axial compression load to study their stress-axial strain and stress-lateral strain characteristics upon loading. Mode of failure of the cylinders has been observed. The results indicated that the confined cylinders have higher ultimate load-capacity and ductility compared to the unconfined cylinders. It also shows that higher strength of steel straps will increase the strength and ductility of confined high strength concrete. Further work needs to be carried out to ascertain the effectiveness of using low-cost steel straps as alternative to more costly confining materials such as Fibre-reinforced plastic (FRP).